Synthesis of water-soluble anthracene-appended benzoxaboroles and evaluation of their cis-1, 2-diol recognition properties. Issue 25 (6th June 2018) - Kusano, S.; Konishi, S.; Yamada, Y.; Hayashida, O.
Abstract : The binding studies of anthracene-appended benzoxaboroles1a–c envisioned the utility of benzoxaborole as a recognition motif of cis -1, 2-diol derivatives in fluorescent probes. Abstract : Three series of water-soluble anthracene-appended benzoxaboroles1a–c were developed; their binding affinity toward cis -1, 2-diols was explored by conventional fluorescence titrations to demonstrate the role of benzoxaborole as a general recognition motif of cis -1, 2-diols for fluorescent probes. The complex structures of the tetra-coordinated boronate adducts between1 and the cis -1, 2-diols were revealed.